2003
DOI: 10.1097/01.ju.0000091876.13656.2e
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Clinical Impact of Biochemical Recurrence of Prostate Cancer 5 or More Years After Radical Prostatectomy

Abstract: Patients are at prolonged risk for BF and CF following RP. Regardless of the timing of the initial PSA recurrence the PSA doubling time is the most powerful predictor of progression, stratifying patients with BF into high and low risk groups for CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(141 citation statements)
references
References 21 publications
10
125
2
4
Order By: Relevance
“…Carver et al, 2006 reported on a population of men with T3 prostate cancer who underwent radical prostatectomy, only 36% with PSA biochemical failure had disease progression. Ward et al, 2003 found that in a population of 3897 radical prostatectomy patients, only 8.3% of the men with PSA biochemical failure died of prostate cancer. Thus PSA failure is associated with prostate cancer-specific death but the majority of men with PSA biochemical failure will die of other causes.…”
Section: Tmprss2:erg F Demichelis Et Almentioning
confidence: 99%
“…Carver et al, 2006 reported on a population of men with T3 prostate cancer who underwent radical prostatectomy, only 36% with PSA biochemical failure had disease progression. Ward et al, 2003 found that in a population of 3897 radical prostatectomy patients, only 8.3% of the men with PSA biochemical failure died of prostate cancer. Thus PSA failure is associated with prostate cancer-specific death but the majority of men with PSA biochemical failure will die of other causes.…”
Section: Tmprss2:erg F Demichelis Et Almentioning
confidence: 99%
“…The study population was not planned in advance, since this was a pilot study aiming to evaluate primarily the feasibility, safety, and morbidity profile of the technique. Moreover, the absence of an extended follow-up could be considered another limit since significant disease recurrence may occur with extended follow-up [24]. However, our outcomes could be used to design a prospective randomized trial, with adequate statistical power, comparing HIFU vs. SRT in the treatment of the palpable, local recurrence of CaP after RP.…”
Section: Discussionmentioning
confidence: 99%
“…8,12,26,27 We did not find these factors to be significantly associated with death from prostate cancer in patients with a PSM, and in fact it is important to note that previous series correlated these features with BCR. Given the documented heterogeneous natural history of BCR, 16,18,19 we sought to identify the association of various clinicopathological features with SP and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8,[10][11][12][13][14][15] Importantly, the use of BCR as a clinical outcome measure remains questionable, as the natural history of BCR is variable. That is, although approximately 35% of patients experience PSA failure within 10 years following RRP, 16,17 BCR does not always translate into systemic progression (SP) and prostate cancer death. 16,18,19 Furthermore, given the sensitivity of PSA to detect disease recurrence following RRP, the clinical course of patients with BCR is generally prolonged, and in fact, median survival has been found not to have reached 15 years after initial PSA failure in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation